2 - Le syndicalisme étudiant, des origines à nos jours : un acteur permanent dans l’évolution socio-politique du Burkina Faso - Bianchini, Pascal; Korbéogo, Gabin (Journal of Higher Education in Africa, 2008)
Emerging from the pre-independence student union, the Fédération des étudiants d’Afrique noire en France (FEANF), the first student organisations in Upper Volta (Burkina Faso) were organised outside the colony in France in the 1950s and Dakar in the 1960s. Student activism developed at the University of Ouagadougou, with phases of activism and intense politicisation (in the 1970s) and then a rela- tive downturn (in the 1980s and the ‘emergency regime’). During the 1990s one saw the renewal of student mobilisation in a context characterised by the increase in demands for the democratisation of the political system and opposition to struc- tural adjustment programmes which threatened the ‘privileged’ status of students. This ‘permanent militancy’ can be explained both by social factors (the working class and rural background of students) and cultural (experiences formerly ac- quired). It is necessary also to consider the particular trajectory of politics in Burkina Faso since the ruling class has always been compelled to incorporate certain im- portant opposition forces, especially unions. The student movement is part of these complex counter-hegemonic forces. It has played a crucial role in supporting these elements in two respects: directly as an avant-garde in popular mobilisations and indirectly as a seed-bed of activism for the political and trade union opposition.